The effectiveness of incorporating metacognitive prompts in collaborative writing on academic English writing skills. Issue 3 (20th January 2021) - Teng, Mark Feng
Abstract: Research shows that acquisition of writing skills can be supported by metacognitive strategy training. However, research on incorporating metacognitive guidance for collaborative writing is scarce. The current study explores the potential effectiveness of incorporating metacognitive prompts, that is, a form of metacognitive guidance, into collaborative writing on academic English writing skills. This study involves four instructional methods, that is, collaborative writing combined with embedded metacognitive guidance (COLL+META), metacognitive training without collaborative writing (META), collaborative writing without metacognitive training (COLL), and individual learning (CG). The dependent variables were students' four academic writing skills, that is, reproduction of text structure knowledge, application of text structure knowledge, reduction of text content, and abstract writing. Participants included 160 students who were learning English as a foreign language (EFL) at a university in mainland China. The participants in each condition received 16 weeks of treatment sessions. The results revealed the improvement from pre‐test to post‐test, supporting the main effects of each learning condition on the four academic writing skills. The results also showed that the COLL+META students demonstrated significantly higher scores in the four academic writing skills than students in the other conditions. This study underlines the importance of incorporating metacognitive strategies for collaborative writing in developing academic writing skills for university EFL students. This study also highlights the potential in applying educational psychology theories for English education.